2020
DOI: 10.1051/e3sconf/202015908007
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Thoracoscopic Radiofrequency Epicardial Ablation with a Bipolar Electrode During Longstanding Persistent form of Atrial Fibrillation

Abstract: Thoracoscopic ablation using the ‘box lesion’ technique was performed using a bipolar radio frequency clamp. A total of 48 patients, including 38 men and 10 women, mean age 58 years (range 33 74). The mean duration of AF was 4 yrs (range 1.5 months 21), the mean size of the atrium 4.15 ± 0.9 cm (2.9-8.8 cm), mean LVEF was 57.7% (39 -73%). Mitral regurgitation of 1-2 degrees was present in 14 patients, EDV LV 147.7 ml (81-224). Primary catheter ablation was performed in 22 patients, where 5 of them (22,7%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Numerous controlled clinical trials indicate herpesvirus reactivation in patients with CFS, confirmed by positive leukocyte PCR results 3,7,8,24–28 . Another group of studies reports an abnormal immune response to activating proteins of the virus.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Numerous controlled clinical trials indicate herpesvirus reactivation in patients with CFS, confirmed by positive leukocyte PCR results 3,7,8,24–28 . Another group of studies reports an abnormal immune response to activating proteins of the virus.…”
Section: Discussionmentioning
confidence: 94%
“…23 Numerous controlled clinical trials indicate herpesvirus reactivation in patients with CFS, confirmed by positive leukocyte PCR results. 3,7,8,[24][25][26][27][28] Another group of studies reports an abnormal immune response to activating proteins of the virus. They are associated with the active reproduction of viral particles in the human body (IgM, IgG to early antigen or p41/38 and IgG to dUTP HHV-6).…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of running on the function of joints is possible only if adequate (not exceeding the capabilities of the motor apparatus) loads are used, and their gradual increase during exercise. The modern experience and development of the rowing and canoeing is characterised by a constant search for more effective means, methods, and organisational forms of training sports reserves (Tuleutaev et al, 2020;Yessentayeva et al, 2021). The main role in the long-term training of athletes is played by the stage of sports improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the experience of usage of another highly active proinflammatory immunomodulatory agent—recombinant interleukin 2—therapeutic immune activation may lead to an undesirable increase in the risk of some autoimmune complications due to impaired immune tolerance to autoantigens [22]. Therefore, the combination of the immunoactivating drug (Propes) with the anti‐inflammatory tolerogenic immunotropic agent (Inflamafertin) seems to be a reliable guarantee of achieving a safe immunomodulatory effect of the applied immunotherapeutic interventions in GDFC patients with selective deficiency of NK and/or NKT cells [23, 24].…”
Section: Introductionmentioning
confidence: 99%